Postintervention Dyspnea after Radiofrequency Catheter Ablation: Think of a Phrenic Nerve Injury. (4th October 2017) - Ramos-Villalobos, Liliana E.; Colin Lizalde, Luis; Márquez, Manlio F.; Iturralde, Pedro; Castillo, Francisco
Abstract : Phrenic nerve injury (PNI) is a rare complication of catheter ablation therapy, most commonly observed in cryoablation of the right side pulmonary veins. We present a case of PNI after radiofrequency catheter ablation that developed acute dyspnea 24 hours after the intervention. Dyspnea is the main symptom of PNI, so the diagnosis should always be suspected if it appears after any type of catheter ablation involving the trajectory of the phrenic nerve. There is no specific treatment for PNI. The only maneuver that has been reported to accelerate the recovery of PNI is early stopping of the ablation therapy.